FAMILY CEREMONIES AND TRADITIONS OF THE LO‘LI PEOPLE OF THE SURKHAN VALLEY - Mashxura Ruziyeva (Scholar Express Journal, 2025)
This article examines the family ceremonies and traditions of the Luli people in the Surkhan Valley. It explores the cultural, social, and historical dimensions of these customs, emphasizing their role in preserving ethnic identity and strengthening family bonds. The study focuses on wedding rituals, birth ceremonies, and other significant family events, demonstrating how these traditions have been preserved and adapted over time. Research is based on fieldwork, interviews with local residents, and historical sources.
Keywords: Luli people; Surkhan Valley; family traditions; wedding rituals